Addressing unresolved tensions to build effective partnerships: lessons from an Aboriginal cancer support network. Issue 1 (December 2015) - Cuesta-Briand, Beatriz; Bessarab, Dawn; Shahid, Shaouli; Thompson, Sandra
Abstract Background Cancer is the second leading cause of death among Aboriginal and Torres Strait Islander people and their survival once diagnosed with cancer is lower compared to that of other Australians. This highlights the need to improve cancer-related health services for Indigenous Australians although how to achieve this remains unclear. Cancer support groups provide emotional and practical support, foster a sense of community and belonging and can improve health outcomes. However, despite evidence on their positive effects on people affected by cancer, there is scarce information on the function and effectiveness of Indigenous-specific cancer peer-support programs in Australia. Using qualitative data from an evaluation study, this paper explores different understandings of how a cancer support group should operate and the impact of unresolved tensions following the establishment of an Indigenous women cancer peer-support network in a regional town in Western Australia. Methods Data were collected through semi-structured interviews with 24 participants purposively selected among Indigenous and mainstream healthcare service providers, and group members and clients. Interviews were audiotaped and transcribed verbatim. Transcripts were subjected to inductive thematic analysis. NVivo was used to manage the data and assist in the data analysis. Rigour was enhanced through team member checking, coding validation and peer debriefing. Results Flexibility and a resistance to formal structuring were at the core of how the group operated. It was acknowledged that the network partly owned its success to its fluid approach; however, most mainstream healthcare service providers believed that a more structured approach was needed for the group to be sustainable. This was seen as acting in opposition to the flexible, organic approach considered necessary to adequately respond to Indigenous women's needs. At the core of these tensions were opposing perspectives on the constructs of 'structure' and 'flexibility' between Indigenous and non-Indigenous participants. Conclusions Despite the group's achievements, unresolved tensions between opposing perspectives on how a support group should operate negatively impacted on the working relationship between the group and mainstream service providers, and posed a threat to the Network's sustainability. Our results support the need to acknowledge and address different perspectives and world views in order to build strong, effective partnerships between service providers and Indigenous communities.